Gelatin From Cartilage of Siberian Sturgeon (Acipenser baerii): Preparation, Characterization, and Protective Function on Ultraviolet-A-Injured Human Skin Fibroblasts - Zhang, Zhe; Wang, Yu-Mei; Qiu, Yi-Ting; Chi, Chang-Feng; Luo, Hong-Yu; Wang, Bin (Frontiers in Marine Science, 2022)
For full use of the by-products during Siberian sturgeon (Acipenser baerii) processing, gelatin was extracted from the cartilages using hot water methods and its physico-chemical properties and protective function on ultraviolet-A injured human skin fibroblasts (HFSBs) were measured. Using single factor and orthogonal experiments, the conditions for extracting gelatin from Siberian sturgeon cartilage were optimized as extraction time 7 h, pH 9, material to liquid ratio (g:mL) 1:5, and temperature 45 °C. The prepared gelatins (TCG) with the yield of 28.8±1.53% had Gly (307 residues/1000 residues) as the major amino acid and contained lower content (214 residues/1,000 residues) of imino acids than that (227 residues/1,000 residues) of pigskin gelatin (PSG). SDS-PAGE, UV, and IR analysis indicated that TCG had the main spectral characteristics of fish gelatin and contained α chains (α1 and α2 chains) and β chain of Type I collagen, but its structure stability was lower than that of PSG due to its low content of imino acids, which induced more small molecular bands observed in the SDS-PAGE pattern. TCG exhibited lower water content, gel strength, emulsion stability index, foam capacity, foam stability, and water-holding capacity, but higher ash content, transmittance, emulsion activity index and fat-binding capacity (P < 0.05). Moreover, TCG could significantly protect HFSBs against ultraviolet-A injury by enhancing the activity of antioxidases (SOD, GSH-Px, and CAT) to scavenge excess reactive oxide species and decrease the content of malondialdehyde. Therefore, gelatin from Siberian sturgeon cartilages could act as promising candidates applied in health-promoting products against ultraviolet-A injury.